The expression of PD-L1 on tumor-derived exosomes enhances infiltration and anti-tumor activity of αCD3 × αPD-L1 bispecific antibody-armed T cells - Cho, Jaewon; Tae, Nara; Song, Yujeong; Kim, Chae Won; Lee, Seung Joo; Ahn, Jae Hee; Lee, Kwang Ho; Lee, Byung Hyun; Kim, Byung Soo; Chang, Sun Young; Kim, Dae Hee; Ko, Hyun Jeong (Cancer Immunology, Immunotherapy, 2024)
Anti-cluster of differentiation (CD) 3 × α programmed death-ligand 1 (PD-L1) bispecific T-cell engager (BsTE)-bound T-cells (BsTE:T) are a promising new cancer treatment agent. However, the mechanisms of action of bispecific antibody-armed activated T-cells are poorly understood. Therefore, this study aimed to investigate the anti-tumor mechanism and efficacy of BsTE:T. The BsTE:T migration was assessed in vivo and in vitro using syngeneic and xenogeneic tumor models, flow cytometry, immunofluorescence staining, transwell migration assays, microfluidic chips, Exo View R100, western blotting, and clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 technology. In murine B16 melanoma, MC38 colon cancer, and human multiple myeloma cells, BsTE:T exhibited superior tumor elimination relative to that of T-cells or BsTE alone. Moreover, BsTE:T migration into tumors was significantly enhanced owing to the presence of PD-L1 in tumor cells and secretion of PD-L1-containing exosomes. Furthermore, increased infiltration of CD44highCD62Llow effector memory CD8+ T-cells into tumors was closely associated with the anti-tumor effect of BsTE:T. Therefore, BsTE:T is an innovative potential anti-tumor therapy, and exosomal PD-L1 plays a crucial role both in vitro and in vivo in the anti-tumor activity of BsTE:T. Graphical abstract: (Figure presented.)
Keywords: Animals; Antibodies, Bispecific; B7-H1 Antigen; CD3 Complex; Cell Line, Tumor; Cell Movement; Exosomes; Female; Humans; Lymphocytes, Tumor-Infiltrating; Melanoma, Experimental; Mice; Mice, Inbred C57BL; T-Lymphocytes; Xenograft Model Antitumor Assays; Bispecific T-cell engager; Exosomal programmed death-ligand 1; Immunotherapy; Programmed death-ligand 1